2015
DOI: 10.5897/jene2014.0492
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of rodents in Alage, Southern Ethiopia

Abstract: An ecological study on population structure of rodents was conducted in Alage, Southern Ethiopia. Sherman live traps were used to capture rodents in four habitats and trapping sessions. A total of 684 rodents that represented 11 species were captured. Regarding population size and density, Mastomys natalensis was the dominant species followed by Arvicanthis dembeensis while the least was observed in Graphiurus murinus in the study period. The highest biomass was recorded in A. dembeensis (6771.43 g/ha) followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…This can be explained by the fact that the open forest in BFR were mostly either swampy or waterlogged in the wet season, both of which are unsuitable for small mammals. This finding is contrary to the study by Addisu and Bekele (2015) which indicated that habitat‐associated density of rodents was lower in farmlands. However, this finding agrees with studies of Vordzogbe et al (2005) and Nyirenda et al (2020) who reported higher abundance of small mammals in farmlands.…”
Section: Discussioncontrasting
confidence: 99%
“…This can be explained by the fact that the open forest in BFR were mostly either swampy or waterlogged in the wet season, both of which are unsuitable for small mammals. This finding is contrary to the study by Addisu and Bekele (2015) which indicated that habitat‐associated density of rodents was lower in farmlands. However, this finding agrees with studies of Vordzogbe et al (2005) and Nyirenda et al (2020) who reported higher abundance of small mammals in farmlands.…”
Section: Discussioncontrasting
confidence: 99%